Virtual reality and its impact on the industrial product (Al-Academy, 2023)
The current study investigates the impact of virtual reality technology on industrial product design. The focus of this study is on the development of industrial products that utilize virtual reality technology, specifically examining the effects of this technology on the visual and design aspects of these products. The aim is to continuously improve the functionality of industrial products and enhance the user experience through virtual reality integration.The first chapter of the study addresses the research problem, which centers around exploring the technological influence of virtual reality used in industrial products and understanding the functionalities it brings to the design process. Virtual reality technology facilitates the activation of user's mental imagery and imagination, thereby highlighting the technological transformation in these products. Based on this, the study formulates the research problem that raises several questions, primarily concerning the extent to which virtual reality technology enhances the functionalities of industrial products.The study's significance lies in uncovering the various applications of virtual reality technology in industrial products, leading to improvements in design, performance, and user experience. Additionally, the study aims to comprehend the impact of virtual reality on industrial product design to enhance their quality and alignment with user needs and expectations.Furthermore, the chapter delves into defining the terms and concepts relevant to the research scope, contributing to establishing the theoretical framework for the study.To achieve the research objectives, the researcher collected the main focal points for analysis based on the theoretical framework, which consisted of three main areas. The first area explored the concept of virtual reality technology in industrial products, identifying various types of this technology and its diverse applications. The second area investigated the effectiveness of functional performance and user interaction with virtual reality products. Finally, the third area reviewed the impact of virtual reality technology on the functional performance and structural composition of industrial products, leading to the identification of key indicators derived from the theoretical framework.In the third chapter, the research procedures and sample selection method were elucidated. The sample was deliberately chosen in alignment with the research objectives and methodology. The descriptive-analytical approach was adopted for the case study, considering its suitability for the research topic. The sample consisted of electronic computer manufacturing companies.Moving on to the fourth chapter, it presented the findings and conclusions drawn by the researcher. Subsequently, the chapter included recommendations, proposals, and a list of references used in the study